Young Adults’ Sleep Duration on Work Days: Differences between East and West - Lo, June C.; Leong, Ruth L. F.; Loh, Kep-Kee; Dijk, Derk-Jan; Chee, Michael W. L. (Frontiers in Neurology, 2014)
Human sleep schedules vary widely across countries. We investigated whether these variations were related to differences in social factors, morningness-eveningness (ME) preference, or the natural light-dark cycle by contrasting the sleep duration and timing of young adults (age: 18-35 years) on work and free days in Singapore (n = 1898) and the UK (n = 837). On work days, people in Singapore had later bedtimes, but wake times were similar to the UK sample, resulting in shorter sleep duration. In contrast, sleep duration on free days did not differ between the two countries. Shorter sleep on work days, without compensatory extra long sleep hours on free days, suggest greater demands from work and study in Singapore. While the two samples differed slightly in ME preference, the associations between eveningness preference and greater extension in sleep duration as well as delays in sleep timing on free days were similar in the two countries. Thus, differences in ME preference did not account for the differences in sleep schedules between the two countries. The greater variability in the photoperiod in the UK was not associated with more prominent seasonal changes in sleep patterns compared to Singapore. Furthermore, in the UK, daylight saving time did not alter sleep schedules relative to clock time. Collectively, these findings suggest that differences in social demands, primarily from work or study, could account for the observed differences in sleep schedules between countries, and that in industrialized societies, social zeitgebers, which typically involve exposure to artificial light, are major determinants of sleep schedules.